Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing (University of Jyväskylä; Vuokatti Sports Technology Unit of the Faculty of Sport and Health Sciences of the University of Jyväskylä, 2020)
The book presents research papers of the 8th International Congress on Science and Skiing which was held at the Vuokatti Sport Resort located in the North-East of Finland, March 11-15, 2019. The congress was hosted by the Vuokatti Sports Technology Unit of the Faculty of Sport and Health Sciences, University of Jyväskylä, Finland. The congress program offered a comprehensive overview of current research in alpine and nordic skiing. The scientific event involved research in topics such as biomechanics in alpine skiing, physiology and training in cross-country skiing & biathlon, talent and injury in skiing, paralympic skiing, cross-country skiing, ski jumping, air drag and aerodynamics in skiing and methodology and technology in skiing.